ANALISIS PEMAHAMAN KONSEP MEAN, MEDIAN, DAN MODUS MELALUI PEMBELAJARAN KONTEKSTUAL DI SD NGABEYAN 01 - Ahmad; Miftahudin; Budi Murtiyasa; Nining Setyaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyse students' ability to understand and solve data processing problems, especially on mean (average), median (middle value), and mode (most frequently occurring value). The form of research used is descriptive qualitative with data collection techniques in the form of observation and in-depth interviews and documentation. analysis techniques using the Miles and Huberman interactive model. The results showed that students had understood the basic concept of median and were able to solve problems independently with good accuracy. On mean material, students have an understanding of the concept but still need encouragement and direction from the teacher in the process of solving problems, especially when facing more data and more complex work steps. On mode, students can identify the most frequently occurring value correctly but have not been able to think analytically so that the answers given are still inaccurate. The interactive and contextual learning process proved effective in helping APs deepen their understanding of concepts and improve their critical and analytical thinking skills. The implication of this finding is the need for reinforcement and continuous practice to increase APs' independence and confidence in solving data processing problems.Keywords: Contextual Approach, Mean, Median, Modus